Effect of Methanolic Extract of Scrophularia subuphylla on Ischemia and Reperfusion-Induced Myocardial Injury - Haleh Vaez; Alireza Garjani; Abbas Delazar; Maryam Rameshrad; Negisa Seyed Toutounchi; Elhameh Nikkhah; Parina Asgharian (Tabriz University of Medical Sciences, 2018)
Background: Coronary artery disease is a leading cause of death worldwide. The present study has been designed to investigate efficacy of methanolic extract of Scrophularia subuphylla (S. subuphylla) on ischemia and reperfusion-induced myocardial injury in isolated rat heart. Methods: The isolated male Wistar rat hearts (n= 5) were perfused by Krebs-Henseleit solution enriched with the extract (0, 1, 5, and 10 μg/ml), using the langendorff method. After 15 minutes stabilization, the hearts were subjected to 30 minutes regional ischemia and then 120 minutes reperfusion. Results: Administration of the extract did not improve any of cardiac markers of flow rate, heart rate and developed pressure. Number, percentage and duration of arrhythmias were not affected by any concentrations of the extract. However, the concentration of 1 and 5 µg/ml increased the VT duration compared to control group (P<0.05). Furthermore, there was not considerable infarct size difference between none of the groups. Methanolic extract did not show any cardioprotective effect, while it had high anti-oxidant activity as well as high amounts of total phenol and flavonoid contents. Conclusion: Generally, the methanolic extract of S. subuphylla at the doses which studied exhibited no protective effects against I/R-induced injures, which might be due to the high amount of cardiac glycosides with low therapeutic index.